Advanced promising routes of carbon/metal oxides hybrids in sensors: A review. (10th March 2018) - Goldoni, Andrea; Alijani, Vajiheh; Sangaletti, Luigi; D'Arsiè, Lorenzo
Abstract: This review focuses on the recent developments of carbon/metal oxide hybrids for gas and biological sensing, which is one of the most important fields where these hybrids are efficiently applied. Carbon and metal oxides are excellent complementary materials: in hybrids, they compensate for the shortcomings of the single components and their combination creates new advantageous features. Intensive research has advanced the understanding of these materials, however, the complex array of possible carbon nanostructure shapes and different metal oxides present many unexplored areas. Current results are already exciting and promise even bigger improvements in sensing. We introduces the recent progress in this field and the key advantages of some nanostructures over each counterpart are discussed and compared, presenting examples and emphasizing the most promising routes.